Dipole reversal: an ictal feature in a patient with benign partial epilepsy of childhood with centrotemporal spike - Délrio F. Silva; Márcia Marques Lima; Renato Anghinah; Edma R Zanoteli; José Geraldo C. Lima (Arquivos de Neuro-Psiquiatria)
We describe the case of a 15-year-old boy who had the diagnosis of benign partial epilepsy of childhood with centrotemporal spike. During the EEG a subclinical electrographic seizure was recorded. The discharges were clearly electropositive in T4 with positive phase reversal between derivations F8-T4 and T4-T6. The whole episode lasted less than one minute (45 sec). The interictal right medio-temporal spikes reemerged after 60 sec and were electronegative in the same location after the end of the electrographic seizures. The mechanisms underlying this uncommon pattern on EEG is not well stablished.